Alleviating physical and psychological symptoms associated with menopause among women in rural areas - Iman Mohammed Mustafa; Shireen Safar Mousa (UIN Maulana Malik Ibrahim Malang, 2026)
This investigation aimed to examine the efficacy of a specifically developed educational program designed to reduce physical and psychological manifestations associated with the menopausal transition among women residing in rural communities. The research utilized a quasi-experimental methodology employing both experimental and control populations, where the study sample comprised 28 women between 45-60 years of age from residents of Moqbli and Karesh villages within Duhok governorate. Participants were allocated into an experimental cohort (15 women) and a control cohort (13 women). An intensive educational curriculum consisting of 8 instructional sessions distributed across two successive weeks was administered to the experimental group. The researchers constructed comprehensive menopause symptom assessment scales alongside physiological assessment of cortisol levels through ELISA testing, specifically tailored for this investigation to evaluate intervention effectiveness. Findings demonstrated statistically significant differences between experimental and control groups, favoring the experimental participants, confirming the educational program's effectiveness in reducing menopausal manifestations. The educational program was specifically designed to target the neurochemical changes that directly affect sleep, mood, cognition, and memory through comprehensive stress management techniques, relaxation exercises, and lifestyle modifications that support hormonal balance and neurotransmitter stability. The study advocates for broader implementation of such educational curricula in rural communities and advancement of specialized supportive services for menopausal women in underserved populations. KEY WORDS: menopause; educational program; rural women; symptom management; health intervention; cortisol; neurochemical changes Copyright ©2026. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0